Where the Sun Rises in the East: (Post-)Communist Remembrance in Germany’s Right-Wing Counter-Public Sphere - Fiedler, Anke (Javnost-The Public, 2023)
This article uses qualitative discourse analysis to examine how the (post-)communist past is remembered in right-wing counter-publics. If memory serves the historical legitimation of the political order, its challengers would be expected to use this part of history to prove the legitimacy of an alternative order. The memory discourse of the German Democratic Republic (GDR) and German unity in the newspaper Junge Freiheit and the magazine Compact serves as a case study. Both publications consider themselves mouthpieces of a far-right readership in Germany and represent positions close to that of the Alternative für Deutschland (AfD). The results show that hegemonic narratives can be found in both publications but that the East and its history are discursively valorised. Against the backdrop of the failure to develop an all-German post-communist memory culture, this article provides clues as to which “historical” arguments fall on fertile ground in right-wing counter-publics and help grow right-wing politics.